Novel synthesis and electrochemical investigations of ZnO/C composites for lithium-ion batteries - Thauer, Elisa; Zakharova, G. S.; Andreikov, E. I.; Adam, Viktor; Wegener, Simon; Nölke, Jan-Hinrich; Singer, Lennart; Ottmann, Alexander; Asyuda, A.; Zharnikov, Michael; Kiselkov, D. M.; Zhu, Q.; et al. (Journal of materials science, 2021)
For the first time, ZnO/C composites were synthesized using zinc glycerolate as a precursor through one-step calcination under a nitrogen atmosphere. The effect of the heat treatment conditions on the structure, composition, morphology as well as on the electrochemical properties regarding application in lithium-ion batteries are investigated. The products obtained by calcination of the precursor in nitrogen at 400—800 °C consist of zinc oxide nanoparticles and amorphous carbon that is in-situ generated from organic components of the glycerolate precursor. When used as anode material for lithium-ion batteries, the as-prepared ZnO/C composite synthesized at a calcination temperature of 700 °C delivers initial discharge and charge capacities of 1061 and 671 mAh g−1 at a current rate of 100 mA g−1 and hence 1.5 times more than bare ZnO, which reaches only 749/439 mAh g−1. The native carbon improves the conductivity, allowing efficient electronic conductivity and Li-ion diffusion. By means of ex-situ XRD studies a two-step storage mechanism is proven.